Applying Water Quality Index Technique to Estimate the Euphrates River Suitability for different uses in Samawa and Nasiriya, Southern Iraq - Hussein, Marwa M.; Al-Dabbas, Moutaz A. (Iraqi Journal of Science, 2023)
Water salinity assessment is fundamental to the management of water resources. The objective of this research is to calculate the water quality index of the Euphrates River by using mathematical methods. As well as to evaluate the water for various uses by estimating the inorganic pollution in the river water in two sites: Samawa and Nasiriya sites. Based on physiochemical characteristics such as pH, TDS, EC,  and concentrations of the major ions of calcium (Ca2+), sodium (Na+), magnesium (Mg2+), potassium (K+), sulphate (SO42-)  and Chloride (Cl-), bicarbonate ions (HCO3-), and minor elements of nitrate (NO32-) and total hardness (TH) were applied in this research for the period from the year 2005 to 2021. The results showed that the predominant ions are SO42- and Ca2+ ions in Samawa, while in Nasiriya, the predominant ion are Mg2+ and SO42- ions. According to international and Iraqi standards, the results indicated that water at these two sites along the Euphrates  River are unsuitable for drinking. It is low alkalinity and very hard water. Although, the water at these two sites is moderate saline and very good for livestock uses and of doubtful water class, based on Todd’s method of Na % for irrigation water.